CONTRA FINE SG-CONTINUOUS MAPS IN FINE TOPOLOGICAL SPACE - Begam, K.Safina (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Powar P. L. and Rajak K. have introduced fine-topological space which is a special case of generalized topological space. Aim of this paper is we introduced in fine sg open sets in fine topological space and also we studied about we investigate properties of contra-F-sg-continuous maps in fine topological spaces Keywords: Fsg-open sets, Fsg-closed set, contra-Fine semi-continuous maps, contra-F-sg-continuous maps AMS Mathematical Subject classification (2010): 54C08, 54C10